1996
DOI: 10.1210/endo.137.6.8641171
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the insulin-like growth factor system by acute acidosis.

Abstract: Many catabolic conditions are characterized by disturbances in acid-base balance and concomitant alterations in the insulin-like growth factor (IGF) system. However, the influence of acidosis per se on the various components of the IGF system has not been extensively examined. The purpose of the present study was to determine the effect of acute metabolic acidosis on the plasma and tissue concentrations of IGF-I and the various IGF-binding proteins (IGFBPs). Conscious unrestrained fasted rats were infused iv w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, we report that NSE/hIL-6 mice show shortened plasma IGF-I half-life and accelerated IGF-I clearance. The latter observation is in agreement with studies in animals showing that conditions with low levels of IGFBP-3 are associated with a marked decrease in IGF-I half-life and accelerated clearance leading to low IGF-I levels even in the presence of normal liver IGF-I production (24,44). Further supporting a direct relationship of IGFBP-3 levels with IGF-I, we found that IGFBP-3 levels were directly correlated with IGF-I levels both in NSE/hIL-6 mice and in patients with s-JIA.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, we report that NSE/hIL-6 mice show shortened plasma IGF-I half-life and accelerated IGF-I clearance. The latter observation is in agreement with studies in animals showing that conditions with low levels of IGFBP-3 are associated with a marked decrease in IGF-I half-life and accelerated clearance leading to low IGF-I levels even in the presence of normal liver IGF-I production (24,44). Further supporting a direct relationship of IGFBP-3 levels with IGF-I, we found that IGFBP-3 levels were directly correlated with IGF-I levels both in NSE/hIL-6 mice and in patients with s-JIA.…”
Section: Discussionsupporting
confidence: 90%
“…35 High NADH/NAD ratio is also characteristic for metabolic acidosis, a condition shown to increase plasma levels of IGFBP-1 and the IGFBP-1 content in the rat liver. 36 Theoretically, normalization of the redox state after alcohol withdrawal might have contributed to the observed reduction in IGFBP-1 levels. It is also possible that the removal of the hepatotoxic agent, ie, alcohol, allows the liver to resume its normal synthetic function and thus normalize IGFBP-1 and Lp(a) production.…”
Section: Discussionmentioning
confidence: 99%
“…It seems unlikely, however, that low levels of insulin/IGF-1 are the sole cause of the signaling abnormalities that we identified. Uremia and acidosis typically have been associated with normal or high insulin levels (2,14,26,(31)(32)(33)(34). Moreover, it is unclear how low values of insulin/IGF-1 would raise the muscle levels of the IRS-2 and PI3-K p85 subunit or increase basal IRS-2-associated PI3-K activity.…”
Section: Discussionmentioning
confidence: 99%